Comparative immunological analyses of whole-sporozoite malaria vaccines - Maia, Teresa Gonçalves Carreira (2022)
Malaria, a mosquito-borne infectious disease, affects hundreds of millions of people yearly. Although an effective malaria vaccine has not yet been found, whole-sporozoite vaccines are the most promising approaches available. In this work, several types of whole-sporozoite vaccines were studied: radiation attenuated sporozoites (RAS), genetically attenuated parasites (GAP) and immunization with sporozoites under chemoprophylaxis (CPS). This thesis aims to broaden the current knowledge about immune responses elicited by whole-sporozoite vaccines via quantitative real time-PCR and flow-cytometry and compare their efficacy against a sporozoite challenge. The parasites studied have different liver stage developments, inducing distinct immune responses. In the CPS approach, parasites are only eliminated in the blood, inducing a strong two-wave type I IFN response, as occurs upon infection with P. berghei parasites. PbΔmei2Δlisp2, a late-arresting GAP induces a weaker type I IFN response, also in two waves. Early-arresting parasites, the GAP PbΔb9Δslarp and RAS, lead to one wave of induction and to the absence of a type I IFN response, respectively. The protection conferred by each parasite studied correlates with its liver stage development: the longer the development, the more effective an immunization is, as long as the parasite is not released to the blood - this seems to negatively affect the immunization efficacy. Also, type I IFN response seems to have a dual effect in whole-sporozoite vaccines, being essential for protection conferred by PbΔb9Δslarp and RAS but deleterious for the protection conferred by CPS. Frequency analysis of mouse liver leucocytes upon immunization revealed, most interestingly, different NKT dynamics depending on the vaccination approach. Further experiments should be performed to elucidate their role in the establishment of protection. This exploratory work represents a contribution for the understanding of mechanisms by which whole-sporozoite immunizations act, allowing for the rising of questions and providing valuable insight to pursue in future studies.